FUNGSI HUMAS DALAM MENINGKATKAN KUALITAS PELAYANAN KESEHATAN PADA RUMAH SAKIT UMUM DAERAH KOTA KENDARI - Sartin, Sartin (Laboratorium Ilmu Komunikasi, Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) Universitas Ha, 2016)
ABSTRACT The purpose of this study was to determine and describe the function of public relations in improving the quality of health care at the Regional General Hospital (RGH) Kendari City. This study used a qualitative descriptive approach and data collection techniques are used interview, observation and document. Data analysis was performed based on primary and secondary data that during the study. The results showed that the function of public relations in improving the quality of health services at the RGH Kendari City, namely: (1) support the activities of the management and the achievement of objectives, supporting the activities of the Regional General HospitalÂ Kendari City began planning, organizing, implementation and evaluation of the work, (2) creating a two-way communication to the public through the delivery of information or policies important related health services in hospitals and distribute back information from the public to the management RGH Kendari City, (3) serve the public and provide information management, namely PR disseminate needed information public and giving information to leaders in connection with health services in hospitals in the public interest, and (4) fostering a harmonious relationship that PR RGH of Kendari always maintained a public relations internally which is doing a good relationship with the users of health services and fostering good relationships with the users of the service externally as one effort improve the quality of health care at the RGH Kendari City. Keywords: Function, Public Relations, Quality. Care and Health